AV3V lesions reduce the pressor response to L-glutamate into the RVLM - Vieira, A. A.; Colombari, Eduardo [UNESP]; De Luca, L. A.; Colombari, DSD; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2006)
Neurons from the rostral ventrolateral medulla (RVLM) directly activate sympathetic preganglionic neurons in the spinal cord. Hypertensive responses and sympathetic activation produced by different stimuli are strongly affected by lesions of the preoptic periventricular tissue surrounding the anteroventral third ventricle (AV3V region). Therefore, in the present study, we investigated the effects of acute (1 day) and chronic (IS days) electrolytic lesions of the AV3V region on the pressor responses produced by injections of the excitatory amino acid L-glutamate into the RVLM of unanesthetized rats. Male Holtzman rats with sham or electrolytic AV3V lesions and a stainless steel cannula. implanted into the RVLM were used. The pressor responses produced by injections of L-glutamate (1, 5 and 10 nmol/100 nl) into the RVLM were reduced 1 day (9 +/- 4, 39 +/- 6 and 37 +/- 4 mm Hg, respectively) and 15 days after AV3V lesions (13 +/- 6, 39 +/- 4 and 43 +/- 4 mm Hg, respectively, vs. sham lesions: 29 +/- 3, 50 +/- 2 and 58 +/- 3 mm Hg, respectively). Injections of L-glutamate into the RVLM in sham or AV3V-lesioned rats produced no significant change in the heart rate (HR). Baroreflex bradycardia and tachycardia produced by iv phenylephrine or sodium nitroprusside, respectively, and the pressor and bradycardic responses to chemoreflex activation with iv potassium cyanide were not modified by AV3V lesions. The results suggest that signals from the AV3V region are important for sympathetic activation induced by L-glutamate into the RVLM. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: sympathetic; rostral ventrolateral medulla; hypothalamus; hypertension; circumventricular organ